Security Risk Analysis of Active Distribution Networks with Large-Scale Controllable Loads under Malicious Attacks - Jiaqi Liang; Yibei Wu; Jun’e Li; Xiong Chen; Heqin Tong; Ming Ni (Complexity)
With the development of distributed networks, the remote controllability of the distributed energy objects and the vulnerability of user-side information security protection measures make distributed energy objects extremely vulnerable to malicious control by attackers. Hence, the large-scale loads may produce abnormal operation performance, such as load casting/dropping synchronously or frequent and synchronous casting and dropping, and hence, it can threaten the security and stable operation of the distribution networks. First, we analyze the security threats faced by industrial controllable load, civil controllable load, and the gains and losses of attacks on the distribution networks. Considering the factors of cyber attacks, we propose a control model and cyber attack model in active distribution networks (ADNs). And, three types of attacks that the target suffered are defined on the basis of “on” and “off” modes for control. Then, the controllable load was maliciously controlled as the research object, and a suitable scenario is selected. The impact of malicious control of the controllable load on the power supply reliability and power quality of the distribution networks are simulated and analyzed, and risk consequences for different types of attacks are provided.